The functionality of daycare centers and the relationship between education and health: The challenge of intersectoral work based on curricular transversality (Revista Contexto & Educação, 2026)
Prepared in a participatory manner and in dialogue, this investigation analyzes the perspective of professionals in the educational field in relation to the importance of daycare centers and the interconnection between education and health within their environments, considering the impacts of this on society. The main objective is to examine the connection between these fields in order to recognize them as places for the child's integral training, highlighting the transversality in the school curriculum and the importance of integration. The study is descriptive with a mixed approach, using semi-structured and self-administered questionnaires as data collection instruments. Quantitative data were analyzed in Microsoft® Office Excel 2016, with calculations of absolute numbers and percentages according to the sample size, while qualitative analysis was conducted through content analysis and the response saturation technique. The results indicate that daycare centers are still predominantly viewed as places of assistance and care, highlighting the need for better integration between education and health. It is concluded, therefore, that promoting interdisciplinary action in institutions, is essential to reflect on health promotion and education for the emancipation of the individual.
Keywords: Children; Teaching; Intersectoral cooperation; Public policy